(untitled) - Joyner, Amy (Hoboken, N.J., 2007)
IN The eBay Billionaires' Club, you will read thestories of twelve professional eBay merchants whorecognized a great business opportunity on the Internetand pursued it-some at great personal financial risk.In every case, the gamble has paid off. There are some powerful lessons to be learnedfrom these entrepreneurs, whose experiences truly runthe gamut. In the end, what they all have in common is that they started small-and some have purposely decided to stay that way. You'll quickly discover that eBay success really iswithin your reach, because every person in this bookbegan at the very bottom. What's more, a number of them have achievedincredible growth in a relatively short period of time,which should motivate you to stop thinking aboutyour idea and get started on the road to becoming amember of this elite club yourself. Get your highlighters out and fasten your seat belts for a journey that will put you on the road to building your own million-dollar-or perhaps even billion-dollar-eBay business!". From the Introduction to The eBay Billionaires' Club.
Keywords: Internet auctions,Businesspeople,Success in business